GATA3 germline variants in childhood pre-B acute lymphoblastic leukemia: association with CRLF2 overexpression and overweight in Mexican patients - Reyes-León, Adriana; Castro-Vargas, Eduardo; Juárez-Velázquez, Ma. del Rocío; Martínez Anaya, Daniel; Salas-Labadía, Consuelo; Moreno-Lorenzana, Dafné; Galván-Díaz, César Alejandro; López-Santiago, Norma; García-Padilla, Eduardo; García-Guzmán, Alda Daniela; Medina-Vera, Isabel; Pérez-Vera, Patricia (Frontiers in Oncology, 2025)
IntroductionCRLF2 abnormalities are prevalent in Hispanics from the U.S. and Mexican children with pre-B acute lymphoblastic leukemia (ALL). This trait is associated with unfavorable prognosis. Furthermore, SNPs rs3824662 and rs3781093 in GATA3 have been associated with an increased risk of pre-B ALL. In particular, rs3824662 is associated with CRLF2-ALL, with a higher prevalence in Hispanic patients. Additionally, rs3824662 is associated with adipogenesis, since Hispanic patients have a high prevalence of obesity and overweight, it has been suggested that obesity predisposes to CRLF2-ALL.MethodsIn this study, we evaluated rs3824662 and rs3781093 as predisposition markers for pre-B ALL in Mexican children using Taqman probes.ResultsBoth risk alleles were found to be associated with susceptibility to pre-B ALL, predisposition to CRLF2-ALL, overweight status, and overall survival. The risk alleles of both SNPs in Mexican patients were among the most frequent compared with other non-Amerindian populations. SNP rs3824662 and rs3781093 were informative for our patients. Analysis of nutritional status indicated that GATA3 alleles may impact overweight status.DiscussionFurther studies on the relationship between nutritional status and GATA3, as well as analysis of other Amerindian ALL populations, are recommended.